PENGARUH MODEL PEMBELAJARAN DISCOVERY TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MTS KELAS VIII DI KABUPATEN SERANG - Hamidah Hamidah; Vidya Ayuningtyas; Sri Wahyuni (LPPM Universitas Bina Bangsa, 2022)
This research is motivated by the low mathematical problem solving ability of students. It is known based on the results of interviews that students experience difficulties when solving questions.This study aims to: 1) find out whether there are differences in the initial abilities of the experimental class and control class students at MTS Ashhabul Maimanah; 2) whether the problem solving ability of students given discovery model learning is better than the conventional model; 3) How is the effect of discovery learning model on students' mathematical problem solving abilities in class VIII. This research is an experimental quantitative research. Data collection techniques using a problem-solving ability test which amounts to five questions in the form of a description. And the data analysis technique was carried out by normality test, homogeneity test, average difference test, and effect size test. Based on the results of the study, it was found that the problem-solving ability was the average value of the experimental class 78.75 while the control class was obtained by 65 and for t_count = 3,431 > t_table = 1,685 so that was rejected and was accepted. In this study, it can be concluded that: 1) there are differences in the initial abilities of the experimental class and control class students at MTS Ashhabul Maimanah; 2) students' mathematical problem solving ability given the discovery learning model is better than the conventional learning model; 3) the effect of the use of discovery learning models on the mathematical problem solving ability of class VIII students at MTS Ashhabul Maimanah is said to be high